A case report of disappearing pigmented skin lesions associated with pembrolizumab treatment for metastatic melanoma. (1st January 2018) - Wolner, Z.J.; Marghoob, A.A.; Pulitzer, M.P.; Postow, M.A.; Marchetti, M.A.
Summary: Pembrolizumab is an immune checkpoint inhibitor that targets the programmed cell death (PD)‐1 receptor. Common cutaneous adverse side‐effects of PD‐1 inhibitors include maculopapular rash, pruritus, vitiligo and lichenoid skin and mucosal reactions. Here we describe a man in his sixties with metastatic melanoma treated with pembrolizumab who subsequently developed fading or disappearance of pigmented skin lesions, lightening of the skin, and poliosis of the eyebrows, eyelashes and scalp and body hair. Compared with baseline high‐resolution three‐dimensional total‐body photography, we observed fading or disappearance of solar lentigines, seborrhoeic keratoses and melanocytic naevi, suggesting that PD‐1 inhibitors may affect the evolution of these benign skin lesions. With dermatoscopic follow‐up, altered lesions showed either blue‐grey peppering/granularity or fading in colour without other identifiable features. No halo lesions or lesions with surrounding inflammation were identified. One changed pigmented lesion that showed blue‐grey peppering/granularity on dermoscopy was biopsied and interpreted as a macular seborrhoeic keratosis with melanophages. Further studies are required to elucidate the effects of PD‐1 inhibition on benign skin lesions.